Karakterisasi Kekuatan Bending dan Hidrofobisitas Komposit Serat Kulit Waru (Hibiscus tiliaceus) Kontinyu Bermatrik Pati Ubi Kayu - Rianto, Ari; Soeparman, Sudjito; Sugiarto, Sugiarto (Jurnal Rekayasa Mesin, 2011)
The development of biopolymer becomes alternative solution of the waste problem which is mostly produced by synthetic polymer. Biopolymer cassava extract which has big potency to be developed as synthetic polymer alternative. Nevertheless, the basic characteristic which is hydrofilyc and low tensile strength makes the polymer film produced not acceptable to be used as synthetic polymer alternative. The method used in this research was continous fiber biocomposite by pressed hand lay up. The matrix was Wau wood fiber which had layer variety 1,2,3,4 and the fiber directions 0o and 90o. The matrix biocomposite uses cassava extract with addition variation of gliserol 5%,10%,15% of dry weight. The experiment testing used bending test standart ASTM C 393 (1997) and moisture test standart ASTM D570-81. From this research, it was found that the highest bending result on fiber variation 3 layers and 5 % matrix gliserol was 50,58 Mpa. The highest elongation on 15% gliserol+1 layer was 35%. The lowest moisture test occurred on 1% laye and 5% matrix was 39.3%. Keywords: Biocomposite, bending, biopolymer, Waru wood fiber , gliserol.